Beyond the symbol model : reflections on the representational nature of language - Stewart, John, 1941- (SUNY series in speech communication., 1996)
Beyond the Symbol Model: Reflections on the Representational Nature of Language presents arguments on several sides of the contemporary debate over the representational nature of language. Contributors include philosophers, linguists, psychologists, semioticians, and communication theorists from the U.S., Canada, Britain, Northern Ireland, and Israel. The chapters respond to the argument that language can no longer be viewed as a system of signs or symbols, and that a post-semiotic account can be developed from the recognition that language is first and foremost constitutive articulate contact. Three chapters extend this argument, two frame it historically, three disagree, and one contextualizes the "beyond enterprise" itself.